2009
DOI: 10.3354/meps07831
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal boundaries to gene flow between Chaenocephalus aceratus populations at South Orkney and South Shetlands

Abstract: The black-fin icefish Chaenocephalus aceratus is among the most abundant fish species on the Antarctic continental shelves of the Scotia Arc, and Bouvet Island. We genotyped 11 microsatellite loci in C. aceratus population samples from South Orkney, southern South Shetlands, and Elephant Island (northern South Shetlands) collected in 2002 and 2006. This investigation further develops a previous study on the species reporting the presence of one panmittic population in southern South Shetlands and Elephant Isla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 86 publications
1
38
0
Order By: Relevance
“…SigniWcant diVerentiation was also conWrmed with genetic marker sets for C. gunnari populations north and south of the ACC (Kuhn and GaVney 2006), but the island shelves along the southern Scotia Arc had not yet been compared. A recent publication on the genetic population structure of C. aceratus from the southern Scotia Arc based on microsatellites is in agreement with our results and shows that the populations on both sides of the Philip Passage are weakly, but signiWcantly diVerentiated, while migration is still evident (Papetti et al 2009). In our study, signiWcant genetic diVerentiation in C. aceratus was detected with microsatellites, but not with mtDNA sequences.…”
Section: Genetic Structure and Diversitysupporting
confidence: 93%
See 1 more Smart Citation
“…SigniWcant diVerentiation was also conWrmed with genetic marker sets for C. gunnari populations north and south of the ACC (Kuhn and GaVney 2006), but the island shelves along the southern Scotia Arc had not yet been compared. A recent publication on the genetic population structure of C. aceratus from the southern Scotia Arc based on microsatellites is in agreement with our results and shows that the populations on both sides of the Philip Passage are weakly, but signiWcantly diVerentiated, while migration is still evident (Papetti et al 2009). In our study, signiWcant genetic diVerentiation in C. aceratus was detected with microsatellites, but not with mtDNA sequences.…”
Section: Genetic Structure and Diversitysupporting
confidence: 93%
“…Previous studies on notothenioid population structures along the Scotia Arc were based on parasite infestation rates (Kock and Möller 1977;Siegel 1980a), morphometric characters (Kock 1981), and more recently on a variety of genetic markers (e.g. Papetti et al 2009). Studies based on parasite infestation rates revealed diVerences between populations north and south of the ACC in C. gunnari and C. aceratus, but not among populations of C. aceratus and C. rastrospinosus along the southern Scotia Arc (Kock and Möller 1977;Siegel 1980a, b).…”
Section: Genetic Structure and Diversitymentioning
confidence: 99%
“…This is the case of Antarctic waters, where the complex ocean circulating system, which promotes dispersal and connectivity all around Antarctica, contributes to limit genetic differentiation among populations (Matschiner et al 2009;Papetti et al 2009Damerau et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Phenotypic differences have been documented previously between regions in growth parameters and parasite infestation (Siegel 1980;Sosinski and Janusz 2000;La Mesa et al 2004). In C. aceratus, however, gene flow via larval dispersal is likely to counteract genetic drift (Papetti et al 2009;Damerau et al 2012) and, rather than genetic differentiation, the differences highlighted in this study are likely to be more the result of a phenotypic response to the prevailing environmental and ecological conditions.…”
Section: Discussionmentioning
confidence: 88%
“…Microsatellite and mitochondrial markers have been examined as well and showed genetic structuring between the SSI and the SOI. However, differentiation was weak, suggesting high gene flow especially in an eastward direction, periodic restrictions in effective population size and considerable temporal variation, congruent with connectivity through larval dispersal (Papetti et al 2007(Papetti et al , 2009Damerau et al 2012).…”
Section: Introductionmentioning
confidence: 90%